KUTIPRAVESHIK RASAYANA- A REVIEW - Harshit, *Shah; Shah, Sejal Harshit (International Journal of Ayurveda and Pharma Research, 2017)
The Vedas have seriously considered the problem of aging and its prevention. It has been the cherished wish of human race to achieve long life and to live at least 100 year in perfect health; probably this idea at a later stage necessitated the development of complete clinical discipline like Rasayana to deal with the problem of aging, its prevention, and rejuvenation of body. In Sushruta Samhita being a text preliminarily dealing with surgical discipline has discussed different problem of Rasayana therapy in a different way. The most important contribution of Sushruta and Dalhana to development of Rasayana tantra is the classification of Rasayana measures and made Rasayana therapy more practical, applied and useful. One distinct observation made by Sushruta regarding the age factor in selection of the subject for Rasayana therapy is the indication in younger and middle age groups. At the same time, the main aim of Geriatrics is to study the changes in the tissue during the aging process and attempt to make the lives of old persons comfortable. If we compare Rasayana with gerontology we can find the major difference between them. In addition to prevention of ageing, Rasayana is aimed for longevity; maintenance of positive health; the improvement in mental faculties like intelligence, perseverance and memory; and resistance against disease. Rasayana essentially refers to the acceleration of the process of nutrition for the correct condition of the body tissue.